VARIABLE HOUSEHOLD DESIGN AND ADAPTABILITY TO THE BUILT ENVIRONMENT: AN ANALYSIS OF IMPROVING THE ECO EFFICIENCY OF RESIDENTIAL DESIGNS - Shaoqing Wang (Operational Research in Engineering Sciences: Theory and Applications)
This study scrutinizes the enhancement of eco-efficiency in residential design through the lenses of variable house type design and the adaptability of the built environment. It delves into the favourable ramifications of variable house type design on resource and energy utilization, delineates the pivotal role of built environment adaptability in environmental preservation and resource optimization, and expounds on the combined impacts of variable house type design and built environment adaptability. The analysis reveals that variable house type design can mitigate resource wastage, optimize indoor space utilization, curtail energy consumption, and enhance energy efficiency through flexible spatial layout and multifunctionality. Moreover, the concept of built environment adaptability underscores the harmonious integration of buildings with their surroundings, leading to reduced natural resource consumption and fostering sustainable development via green building practices and ecological landscape design. The synergy between these two approaches optimizes eco-efficiency based on the specific environmental context of the building, a benefit that traditional methods cannot achieve. Variable house design offers greater spatial flexibility and potential for adaptability to the built environment, thereby encouraging the use of more environmentally friendly and energy-efficient building materials.  Solar and wind energy, especially, can reduce their consumption rate and increase the range of available energy. Together, variable house type design and building environmental adaptability have a comprehensive impact on improving the eco-efficiency of residential design and provide important ideas and directions for future residential design.